2015
DOI: 10.1016/j.jacc.2015.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Programmed Ventricular Stimulation After Catheter Ablation of Post-Infarction Ventricular Tachycardia

Abstract: Noninducibility after VT ablation in patients with post-infarction VT is independently associated with lower mortality during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
37
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 8 publications
4
37
2
5
Order By: Relevance
“…In particular, unipolar voltage mapping may have even greater sensitivity for identifying subtle areas of abnormality. For example, larger areas of unipolar voltage abnormality were recently shown to predict irreversibility of NICM in patients without scar detected by MRI or bipolar voltage mapping(16).In contrast to a recent multicenter report(17), acute procedural success was not significantly associated with the primary endpoint in our multivariate model (p ¼ 0.06). It is likely that with a larger sample size, the association would have been statistically significant.Through the incorporation of electrophysiological risk factors, we aimed to improve risk stratification of patients with NICM beyond LVEF.…”
contrasting
confidence: 81%
“…In particular, unipolar voltage mapping may have even greater sensitivity for identifying subtle areas of abnormality. For example, larger areas of unipolar voltage abnormality were recently shown to predict irreversibility of NICM in patients without scar detected by MRI or bipolar voltage mapping(16).In contrast to a recent multicenter report(17), acute procedural success was not significantly associated with the primary endpoint in our multivariate model (p ¼ 0.06). It is likely that with a larger sample size, the association would have been statistically significant.Through the incorporation of electrophysiological risk factors, we aimed to improve risk stratification of patients with NICM beyond LVEF.…”
contrasting
confidence: 81%
“…The population in the current study is an extension of a previously published cohort, 6 with the inclusion of one additional VT ablation center and with additional patients and longer follow-up from all centers. All consecutive patients undergoing catheter ablation for infarct-related VT were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…6 Briefly, after informed consent was obtained, programmed stimulation was performed with ≤4 extra stimuli from multiple right ventricular locations with coupling intervals down to 200 ms or refractoriness, whichever occurred first, in an attempt to induce VT unless the patient was in VT at the beginning of the procedure. Clinical VT was defined on the basis of 12-lead electrocardiograms or VT electrogram morphology from ICD recordings.…”
Section: Methodsmentioning
confidence: 99%
“…Ablation techniques aiming at the elimination of the endocardial LPs and scar homogenization have been proven effective in treating VT. [3][4][5][6] Although the VT noninducibility after catheter ablation (CA) is commonly used as a procedural end point, some important limitations question the role of programmed ventricular stimulation (PVS) as a proof of long-term success after ablation. [7][8][9] We suggested that the LPs in SAECG correlate with the endocardial scar area and LPs in electro-anatomic maps of patients with ischemic cardiomyopathy. Further, we hypothesized that substrate-guided ablation and abolition of the endocardial LPs can result in normalization of the SAECG.…”
mentioning
confidence: 91%